2022
DOI: 10.1186/s11671-022-03674-8
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapeutic Effect of Nanostructured Metal Sulfide Photosensitizers on Cancer Treatment

Abstract: Photodynamic therapy (PDT) utilizes photosensitizers (PSs) to produce reactive oxygen species (ROSs) upon irradiation, which causes the shutdown of vessels and deprives the tumor of nutrients and oxygen, and in turn induces adverse effects on the immune system. However, significant efforts are needed to increase the efficiency in PDT in terms of light delivery to specific PSs for the clinical treatment of tumors located deep under the skin. Even though PDT offers a disease site-specific treatment modality, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 97 publications
(143 reference statements)
0
10
0
Order By: Relevance
“…Several PSs have already received FDA approval for use in photodynamic treatment for various types of cancer [2]. The physicochemical and biological characteristics of a PS could be summarized as the following: (1) composition uniformity, purity, and negligible of dark toxicity; (2) high clearance from the body patients [12]; (3) excellent solubility in body tissues; (4) stability at room temperature [9]; (5) potent absorption with a high extinction coefficient at near-infrared (NIR) wavelength range (700-1300 nm), where tissue penetration is increased, and the auto-absorption is reduced by other endogenous molecules (such as the hemoglobin); (6) inexpensive, affordable, and easy to synthesize; (7) the capability of high tumor selectivity and subcellular targeting [16].…”
Section: Photosensitizersmentioning
confidence: 99%
“…Several PSs have already received FDA approval for use in photodynamic treatment for various types of cancer [2]. The physicochemical and biological characteristics of a PS could be summarized as the following: (1) composition uniformity, purity, and negligible of dark toxicity; (2) high clearance from the body patients [12]; (3) excellent solubility in body tissues; (4) stability at room temperature [9]; (5) potent absorption with a high extinction coefficient at near-infrared (NIR) wavelength range (700-1300 nm), where tissue penetration is increased, and the auto-absorption is reduced by other endogenous molecules (such as the hemoglobin); (6) inexpensive, affordable, and easy to synthesize; (7) the capability of high tumor selectivity and subcellular targeting [16].…”
Section: Photosensitizersmentioning
confidence: 99%
“…Moreover, light-induced heating may be utilized to release therapeutic drugs coupled with gold nanoparticles 30 . Altogether, it has been shown that gold nanoparticles may be employed successfully in photodynamic therapy (PDT), in which light is used to promote localized singlet oxygen production 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic PSs have been shown to penetrate more deeply into the cells than hydrophilic ones due to their high lipophilicity [ 15 , 18 ]. As such, many synthetic dyes and natural pigments could be employed as photosensitizers for PDT because they may be less prone to adverse drug interactions [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%